C-Coretractable and Strongly C-Coretractable Modules - Hadi, Inaam Mohammed Ali; Al-Aeashi, Shukur Neamah (Al-Nahrain Journal of Science, 2019)
Let R be a ring with identity and M be an R-module with unity. In this paper we introduce the notion of C-coretractable modules. Some basic properties of this class of modules are investigated and some relationships between these modules and other related concepts are introduced. Also, we give the notion of strongly C-coretractable and study it comparison with C-coretractable.